2007
DOI: 10.1523/jneurosci.5335-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting the Inhibition: A Neuronal Network for Sound Localization in Reverberant Environments

Abstract: The precedence effect describes the phenomenon whereby echoes are spatially fused to the location of an initial sound by selectively suppressing the directional information of lagging sounds (echo suppression). Echo suppression is a prerequisite for faithful sound localization in natural environments but can break down depending on the behavioral context. To date, the neural mechanisms that suppress echo directional information without suppressing the perception of echoes themselves are not understood. We perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
96
2
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(108 citation statements)
references
References 29 publications
9
96
2
1
Order By: Relevance
“…On an intermediate time scale, reversible changes in ILD sensitivity in the gerbil's brainstem lasting several days can be induced by noise exposure (Siveke et al 2007), which may cause homeostatic adaptation to the overall driving force or changes in the turnover and trafficking of receptors, vesicles, and proteins in the postsynaptic machinery (reviews: Bruneau et al 2006, Chen et al 2007. Such explanations only occur over the time course of several hours and are therefore unlikely mechanisms underlying the plasticity observed in this study.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…On an intermediate time scale, reversible changes in ILD sensitivity in the gerbil's brainstem lasting several days can be induced by noise exposure (Siveke et al 2007), which may cause homeostatic adaptation to the overall driving force or changes in the turnover and trafficking of receptors, vesicles, and proteins in the postsynaptic machinery (reviews: Bruneau et al 2006, Chen et al 2007. Such explanations only occur over the time course of several hours and are therefore unlikely mechanisms underlying the plasticity observed in this study.…”
Section: Discussionmentioning
confidence: 84%
“…The response properties established in the superior olive are then reiterated in auditory centres along the ascending neuraxis. However, numerous transformations take place which modify the basic response properties of olivary projections (Pollak et al, 2002;Pecka et al 2007). In this regard, a great deal of attentions has been focussed on the inferior colliculus which integrates a variety of both excitatory and inhibitory ascending inputs from various monaural and binaural brainstem nuclei including olivary inputs (Brunso-Bechtold et al, 1981;Oliver et al, 1995;Hutson et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Pecka et al (2007) reported synaptic GABAergic time constants elicited by a short train of fiber stimulations that may explain the time course of the observed persistent inhibition. This mechanism is further supported by the lack of clear ongoing activity in DNLL neurons for short auditory stimuli in vivo (Siveke et al, 2006;Pecka et al, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…In the ascending pathways on the level of the dorsal nucleus of the lateral lemniscus (DNLL), GABAergic inputs suddenly generate an inhibition of a different time domain. Originating from DNLL neurons (Adams and Mugnaini, 1984;Roberts and Ribak, 1987;Kelly and Kidd, 2000;Burger and Pollak, 2001), this GABAergic inhibition outlasts an auditory stimulus by tens of milliseconds (Yang and Pollak, 1994;Burger and Pollak, 2001;Pecka et al, 2007). Functionally, this persistent inhibition is involved in binaural processing and has been suggested to be a basis for echo suppression Pollak, 1994, 1998;Kelly and Kidd, 2000;Burger and Pollak, 2001;Pecka et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation